How digital technology affects regional energy intensity from the perspective of energy economy: a case study of the Yangtze River economic belt - Gao, Shaokui; Li, Xintao; Duan, Huayang; Liu, Shuchang; Sun, Xuesong (Frontiers in Environmental Science, 2024)
This study aims to explore the impact of digital technology innovation on energy efficiency and energy intensity, and further provide new insights for addressing emerging challenges in energy economics. Focusing on the panel data of 11 provinces and cities in the Yangtze River Economic Belt from 2010 to 2020, this study thoroughly investigates the process by which the digital economy influences regional energy intensity through the mechanism of technological spillovers, utilizing the fixed-effect model, the mediated-effect model, and the spatial Durbin model. The systematic empirical analysis clearly demonstrates that the vigorous development of the digital economy significantly reduces regional energy intensity, and this effect remains stable after tests for endogeneity and robustness. Further analysis reveals that green technology innovation is a crucial pathway through which the digital economy reduces regional energy intensity. Additionally, the digital economy positively and indirectly lowers the energy intensity of neighboring provinces through technological spillovers. However, it is noteworthy that the rapid growth of the digital economy since 2017 has also triggered the so-called "energy rebound effect," which has led to an increase in energy consumption in neighboring regions to some extent. Therefore, to achieve a sustainable reduction in regional energy intensity and promote coordinated regional development, it is essential to continuously strengthen the development of a digital economy centered on digital technology to fully realize its technological spillover effects. These findings not only provide a scientific basis for the formulation of regional energy policies but also offer valuable insights for China in promoting green development and achieving the goals of carbon peaking and carbon neutrality.